Supply chain transparency and willingness-to-pay for refurbished products. Issue 3 (12th August 2019) - Duan, Yanji; Aloysius, John A.
Abstract : Purpose: Researchers in supply chain transparency have called to expand the boundaries by disclosing various types of information to multiple stakeholders. The purpose of this paper is to explore the effect of transparency about supply chain sustainability on consumers as critical stakeholders and investigate the effectiveness of message characteristics. Design/methodology/approach: This study utilizes two scenario-based experiments grounded in a refurbished goods context: Study 1, which employs a 2×2 between-subject experiment investigates the effects of product type and sustainable information provision on consumers evaluations, and Study 2, which employs a 2×1 between-subject experiment examines the effects of sustainable information direction on consumer evaluations. A total of 348 participants were recruited from the Amazon M-Turk platform across the two experiments. Data are analyzed with regression analysis using the PROCESS macro in SPSS and the Johnson–Neyman technique. Findings: Contrary to prior research that assumes that refurbished products are associated with lower quality, quality perceptions are moderated by individuals' environmental involvement (EI) and the information presented by the firm. More importantly, consumer evaluations are influenced by specific characteristics of sustainable supply chain messages: high EI individuals have higher willingness-to-pay a premium (WTPP) when the message is consistent with original beliefs (pro-attitudinal). In contrast to prior theory, there was no difference in the WTPP of consumers with high EI and low EI for counter-attitudinal messages. Practical implications: The study shows that what to say, how to say it and to whom, are critical for firms who seek to nudge consumers to support their sustainable practices. Originality/value: The value of communicating information on sustainability has been well established. However, little is known about such association when the information provided trades off environmental benefits and product quality. This research addresses the gap in a refurbished product context. The research studies the effect of sustainable supply chain transparency and message characteristics on stakeholders' evaluations.